163k views
5 votes
Please prove the following identity

Please prove the following identity-example-1
User GONG
by
7.8k points

1 Answer

7 votes

Let's remember the factorizations


a^3 + b^3 = (a+b)(a^2-ab+b^2)


a^3- b^3=(a-b)(a^2+ab+b^2)

Now


(\sin ^3 \theta + \cos^3 \theta)/(\sin \theta + \cos \theta) + (\sin^3 \theta - \cos^3 \theta)/(\sin \theta - \cos \theta)


=((\sin \theta + \cos \theta)(\sin ^2 \theta - \sin \theta\cos \theta + \cos^2 \theta))/(\sin \theta + \cos \theta) + ((\sin \theta - \cos \theta)(\sin^2 \theta + \sin \theta \cos \theta + \cos^2 \theta))/(\sin \theta - \cos \theta)


=\sin ^2 \theta - \sin \theta\cos \theta + \cos^2 \theta + \sin^2 \theta + \sin \theta \cos \theta + \cos^2 \theta


=\sin ^2 \theta + \cos^2 \theta + \sin^2 \theta+ \cos^2 \theta


=2 \quad\checkmark

User AnnaSm
by
6.9k points